2014
DOI: 10.1002/chem.201400168
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters! On the Way to Ionic Liquid Systems without Ion Pairing

Abstract: Several, partly new, ionic liquids (ILs) containing imidazolium and ammonium cations as well as the medium-sized [NTf2 ](-) (0.230 nm(3) ; Tf=CF3 SO3 (-) ) and the large [Al(hfip)4 ](-) (0.581 nm(3) ; hfip=OC(H)(CF3 )2 ) anions were synthesized and characterized. Their temperature-dependent viscosities and conductivities between 25 and 80 °C showed typical Vogel-Fulcher-Tammann (VFT) behavior. Ion-specific self-diffusion constants were measured at room temperature by pulsed-gradient stimulated-echo (PGSTE) NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 64 publications
10
80
0
Order By: Relevance
“…It is also worth to point out that beyond this ''layering'' of the different ions, the anion and cation have other microscopic properties that show clear differences. For example, it has been shown that the cations have larger mobilities in ILs compared to the anions [28,29], even if the latter particle is significantly smaller in size [30].…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth to point out that beyond this ''layering'' of the different ions, the anion and cation have other microscopic properties that show clear differences. For example, it has been shown that the cations have larger mobilities in ILs compared to the anions [28,29], even if the latter particle is significantly smaller in size [30].…”
Section: Resultsmentioning
confidence: 99%
“…30 Consequently, this observation leads to the conclusion that ion-pairing clearly is less favored in [Al(Ohfip) 4 ] − ILs than in [NTf 2 ] − ILs.…”
Section: Self-diffusion Constants and Ion-pairingmentioning
confidence: 84%
“…3 Again, [Al(Ohfip) 4 ] − ILs prove to be the best subclass with conductivities of up to 4 mS·cm −1 at 25°C. 3,30 As with the viscosities, the effect of exchanging cations is relatively negligible compared with [NTf 2 ] − ILs. 30 Imidazolium-based ILs show superior properties compared with ammonium ILs.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 98%
See 2 more Smart Citations